P2Y12 receptor as a new target for electroacupuncture relieving comorbidity of visceral pain and depression of inflammatory bowel disease - Yanzhen Li; Hong Zhang; Jingwen Yang; Muouyang Zhan; Xuefei Hu; Yongmin Liu; Lingling Yu; Xiaochen Yan; Shangdong Liang; Ruyue Zhang; Ying Lu; Beining Li; et al. (BMC, 2021)
Abstract Background The P2Y12 receptor is a kind of purinoceptor that is engaged in platelet aggregation, and P2Y12 inhibitors have been used in clinical antithrombotic therapy. The P2Y12 receptor in microglia induces interleukin-1β (IL-1β) expression, which is a key mediator of depression in the brain. Although peripheral P2Y12 is involved in neuropathic pain, whether P2Y12 expression in the medial prefrontal cortex (mPFC) is associated with comorbidities of visceral pain and depression remains unclear. Accumulating evidence suggests that electroacupuncture (EA) is effective in treating inflammatory bowel disease (IBD), but its mechanism is unknown. This study aimed to determine whether P2Y12 expression in the mPFC is associated with comorbidities of visceral pain and depression in IBD and whether EA treats IBD by targeting the P2Y12 receptor. Methods We used 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced IBD mice. P2Y12 short hairpin RNA (shRNA) was stereotaxically injected into the bilateral mPFC. EA was performed on bilateral "Dachangshu" (BL25) acupoints once a day for 7 days. Von Frey filaments and colorectal distension were used to detect the mechanical pain threshold and visceral pain sensitivity. The sucrose preference test, tail suspension test and forced swimming test were used to evaluate depression in mice. Western blotting was used to test the expression of P2Y12 and IL-1β. Immunofluorescence staining was used to assess microglial activity. Results We found that IBD mice presented visceral pain and depression associated with increased P2Y12 expression in the mPFC. P2Y12 shRNA significantly attenuated visceral pain and depression in IBD mice. P2Y12 shRNA significantly downregulated IL-1β expression and inhibited the activation of microglia in the mPFC of IBD mice. Meanwhile, EA played a similar role of P2Y12 shRNA. EA significantly downregulated P2Y12 expression, weakened the activation of microglia, and then inhibited IL-1β expression in the mPFC, thus relieving visceral pain and depression in IBD mice. Conclusion The present study provided new ideas that the P2Y12 receptor in the mPFC could be a new target for the treatment of comorbid visceral pain and depression by EA. This may not only deepen our understanding of the analgesic and antidepressant mechanisms of EA but also promote the application of EA to treat IBD.